Blood Glucose Level and HbA1C in Pediatric Patients with Diabetes Mellitus Type 1 - Priatna, Anisha Sefina; Ryadi Fadil, R. Mohamad; Susanto, Nugroho Harry (Althea Medical Journal, 2017)
Background: Diabetes mellitus (DM) is a common disease found all over the world, including Indonesia. The DM often found in pediatric patients is DM Type 1. The DM patients with uncontrolled blood glucose will likely suffer multiple organ damage, most notably to the kidneys, eyes, heart, and nerves. To help monitor blood glucose levels, lab checkups such as fasting blood glucose, 2 hours postprandial, and Hemoglobin A1C (HbA1C) levels are done. The aim of this study was to determine the profile of blood glucose and HbA1C in pediatric patientsÂ with DM Type 1.Methods: The study was held in August to October 2014, using descriptive method and cross sectional design. Data were obtained from 28 medical records of DM Type 1 patients in the Department of Child Health at Dr. Hasan Sadikin General Hospital. The variables of this study were blood glucose level and HbA1 in three consecutive examinations. The collected data was presented in tables.Results: The patients were 19 female and 9 male, most of the patients aged between 11â15 years old. Data reported that on first, second, and third examination, most subjects had both fasting blood glucose and 2 hours postprandial blood glucose levels over 180 mg/dl. On first and second HbA1c checkup, most subjects had values over 10%, and on third checkup had results ranging from 8 to 9.9%.Conclusions: Most patients are girls and aged between 11â15 years old. The most have uncontrolled blood glucoselevel and HbA1c levels.Â DOI:Â 10.15850/amj.v4n2.1074